Manuál Flexible Assertive Community Treatment (FACT) : vize, model, praxe a organizace - Veldhuizen, J. R. van; Bähler, Michiel; Vavřinková, Martina; Stuchlík, Jan (Centrum pro rozvoj péče o duševní zdraví, z. s, 2017)
The manual presents a model of community team psychiatric care for mentally ill patients. Intended for the professional public.
Keywords: Mental Health Services; duševně nemocní; služby péče o duševní zdraví; Persons with Psychiatric Disorders; Quality Assurance, Health Care; Community Health Nursing; Interdisciplinary Communication; týmová péče o pacienty; zajištění kvality zdravotní péče; mezioborová komunikace; komunitní ošetřovatelská péče; management, organizace a řízení zdravotnictví; Patient Care Team; psychiatrie